Genome-Wide Identification and Characterization of Calcium Metabolism Related Gene Families in Arabidopsis thaliana and Their Regulation by Bacillus amyloliquefaciens Under High Calcium Stress - Gong, Jiyi; Shi, Tianlong; Li, Yuke; Wang, Hancheng; Li, Fei (Frontiers in Plant Science, 2021)
Several gene families involved in calcium signaling have been detected in plants, including calmodulin (CaM), calcium dependent protein kinases (CDPK), calcineurin B-like (CBL) and cyclic nucleotide-gated channels (CNGCs). In our previous study, we demonstrated that Bacillus amyloliquefaciens LZ04 (B. amyloliquefaciens LZ04) regulate genes involved in calcium stress in Arabidopsis thaliana (A. thaliana). Here, we aimed to explore the potential involvement of calcium-related gene families in the response of A. thaliana to calcium stress and the potential regulatory effects of B. amyloliquefaciens LZ04 on these genes. The structure, duplication, synteny, and expression profiles of 102 genes in calcium-related gene families in A. thaliana were investigated. Hidden Markov Models (HMMs) and BLASTP were used to predict candidate genes and conserved domains of the candidate genes were confirmed in SMART and NCBI CDD databases. Gene duplications and synteny were uncovered by BLASTP and phylogenetic analysis. The transcriptome expression profiles of candidate genes were investigated by strand-specific sequencing. Cluster analysis was used to find the expression profiles of calcium-related genes families under different treatment conditions. A total of 102 genes in calcium-related gene families were detected in A. thaliana genome, including 34 CDPK genes, 20 CNGC genes, 18 CIPK genes, 22 IQD genes, and 10 CBP genes. Additionally, of the 102 genes, 33 duplications (32.35%) and 26 gene pairs including 48 genes (47.06%) were detected. Treatment with B. amyloliquefaciens LZ04 enhanced the resistance of A. thaliana under high calcium stress by regulating some of the genes in the calcium-related gene families. Functional enrichment analysis revealed that the genes clustered in the 42nd expression profile which may be B. amyloliquefaciens-responsive genes under calcium stress were enriched in protein phosphorylation and protein modification process. Transcriptome data was validated by RT-PCR and the results generally corroborated the transcriptome sequencing results. These results may be useful for agricultural improvement in high calcium stress regions.